Agricultural research, technology and innovation in Africa: Issues and options. (1st March 2020) - Hall, Andy; Dorai, Kumuda
This article deals with the challenges of harnessing agricultural research, technology and innovation in Africa. In particular, it focuses on the ways in which development assistance could adapt to improve impact. A historical review of evolving research methods illustrates the way in which increasing interest in innovation has reframed the research approach. This form of research practice is increasingly being referred to as research for development. While the contours of this approach are still emerging, this paper outlines key practices and principles and suggests how these could be implemented. This styalized view of future practice is then used to discuss the implications of this for the role of different actors in the research, innovation and development assistance landscape. Concluding observations include the lament that despite the large diversity in the types of projects and research practice, there is little consensus on what works and what does not. This lack of systematic efforts to critically assess the performance of different approaches hampers learning and capacity building and holds back more effective deployment of agricultural science technology and innovation in the continent.